La libéralisation des échanges mondiaux et le respect des règles fondamentales en matière sociale : un lien controversé (Note) - Dufour, Sophie (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1995)
At the end of the Uruguay Round talks, the social dimension to world trade liberalization is still a subject of sharp controversy. The question has come up time and again over the last fifty years, particularly in response to certain American initiatives. It never could provide common ground for the interests of all parties present on the international stage. The possibility of agreeing on its raison d'être has seemed, from that point on, impossibly vain. In a context of increasingly deeper economic integration, in which trade liberalization is not inconsequential to domestic industries, the seriousness of the worker protection issue is no longer debatable. The idea of linking the opening of markets to respect for certain basic social standards seems both unavoidable to some and unacceptable to others. The following article casts a retrospective look on the debates raised during the last few decades over what is now commonly called the "social clause".